Calculation of PLS prediction intervals using efficient recursive relations for the Jacobian matrix - Serneels, Sven; Lemberge, Pascal; Van Espen, Pierre J. (Journal of chemometrics, 2004)
Several algorithms to calculate the vector of regression coefficients and the Jacobian matrix for partial least squares regression have been published. Whereas many efficient algorithms to calculate the regression coefficients exist, algorithms to calculate the Jacobian matrix are inefficient. Here we introduce a new, efficient algorithm for the Jacobian matrix, thus making the calculation of prediction intervals via a local linearization of the PLS estimator more practicable. Copyright © 2004 John Wiley & Sons, Ltd.